Determinants of Bank Profitability: The Case of Listed Bank on Indonesian Stock Exchange - Rara Angraini; Mirna Prastiwi (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
Banks are referred to as financial institutions or companies that are authorized by the government to manage money by receiving deposits, providing loans and investments. Banks are important in gaining profits for long-term survival and bank growth. In calculating bank profitability there are various ways, namely by using ROE, ROA and NIM. The dependent variable is profitability with ROE, ROA and NIM measurement tools. Purposive sampling technique is used as a sampling method with criteria: 1) banks listed on the IDX during the observation period from 2008 to 2018, 2) banks during the observation period from 2008 to 2018 and 3) generate positive profit or profitability in a row - according to the years 2008 to 2018. The method of multiple linear regression analysis was used in this study, using the help of SPSS software version 20. Output of research shows descriptive statistics, where the maximum value is in the size variable, while the ROE variable ranks the lowest minimum, with the highest average being the size and the standard deviation